Corrosion resistance and cytotoxicity of a MgF2 coating on biomedical Mg–1Ca alloy via vacuum evaporation deposition method. (2nd April 2013) - Li, N.; Li, Y. D.; Wang, Y. B.; Li, M.; Cheng, Y.; Wu, Y. H.; Zheng, Y. F.
Abstract : To reduce the biocorrosion rate and enhance the biocompatibility by surface modification, MgF2 coatings were prepared on Mg–1Ca alloy using vacuum evaporation deposition method. The average thickness of the coating was about 0.95 µm. The results of immersion test and electrochemical test indicated that the corrosion rate of Mg–1Ca alloy was effectively decreased after coating with MgF2 . The MgF2 coating induced calcium phosphate deposition on Mg–1Ca alloy. After 72 h culture, MG63 cells and MC3T3‐E1 cells were well spread on the surface of the MgF2 ‐coated Mg–1Ca alloy, while few cells were observed on uncoated Mg–1Ca alloy samples. In summary, MgF2 coating showed beneficial effects on the corrosion resistance and thus improved cell response of the Mg–1Ca alloy effectively and should be a good surface modification method for other biomedical magnesium alloys. Copyright © 2013 John Wiley & Sons, Ltd.